Pengaruh Disiplin Kerja, Lingkungan Kerja Fisik dan Budaya Organisasi terhadap Komitmen Afektif Karyawan - Suryawan, Andika Febri; Prayekti, Prayekti; Septyarini, Epsilandri (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of work discipline, physical work environment, and organizational culture on employees' affective commitment to the permanent employees of UST Yogyakarta. This study uses quantitative method. The population in this study were all permanent employees of UST. The number of samples was determined using the Solvin formula while the sampling technique employed accidental sampling technique. The gained data were analyzed using classical assumption test and multiple linear regression. The research findings show that work discipline has a significant positive effect on employee affective commitment with a significance value of 0.039. The physical work environment has a significant positive effect on employee affective commitment with a significance value of 0.043. Organizational culture has a significant positive effect on employee affective commitment with a significance value of 2.699. Simultaneously work discipline, physical work environment, and organizational culture affect the affective commitment of employees.